Condición higiénica sanitaria y calidad microbiológica de carne bovina comercializada en el mercado Belén Iquitos - López Panduro, Carlos Enrique (2024)
The purpose of this study was to determine the relationship between the hygienic-sanitary condition and microbiological quality of the beef marketed in the Belen market - Iquitos, developed through a non-experimental methodology of descriptive-correlational type, where we sought to find a correlation between the variables under study which were: hygienic-sanitary condition and microbiological quality, which were studied in their natural environment by collecting information from 25 people working in the beef stalls of the Belen market in the city of Iquitos: Hygienic-sanitary condition and microbiological quality, which were studied in their natural environment by collecting information from 25 people working in the beef stalls of the Belen Market in the city of Iquitos, to whom the interview technique was applied and a data collection form was used for this purpose, and performing the laboratory analysis of beef samples from the Belen Market and the Municipal Camal, as this is the point of origin from which the raw material comes, for which the analysis of the indicator microorganisms such as the following were carried out: Enumeration of Mesophilic Aerobic Microorganisms, Enumeration of Total Coliforms, Enumeration of Escherichia coli, Enumeration of Staphylococcus aureus and Detection of Salmonella spp, reaching the following results: That better actions should be taken by the personnel working in the sale of beef in the Belen Market so that in the medium to short term there can be a better management of the hygienic-sanitary conditions and on the other hand the final result that the beef that is marketed obtained a high microbial load in Escherichia coli and therefore in Total Coliforms.